Corporate social responsibility and institutional theory - Silva, M. J.; Azevedo, G.; Oliveira, J. (Encyclopedia of sustainable management, 2020)
Corporate social responsibility (CSR) and institutional theory are linked. The fundamental basis of the link between CSR and institutional theory is through legitimacy. One of the features of the CSR practices adoption in business is the voluntary nature. Several authors reflect this fact in the definition of what should be a social responsibility. CSR was defined by the European Commission (2001: 6) as “a concept whereby companies integrate social and environmental concerns in their business operations and in their interaction with their stakeholders on a voluntary basis.” This orientation was reinforced by the European Commission that refers to a better behavior by companies through the adoption of credible and transparent social practices, indicating the transparency like an essential component. In order to achieve responsible business management, the European Commission...